Community based rehabilitation in Vietnam : - Pierdomenico, Lorenzo (Medical Publíhing House, 2008)
The document has been designed for staff at provincial and district levels, responsible for managing and co-coordinating Community-Based Rehabilitation (CBR) activities. The aim of the document is to suggest to the local authorities, as well as to NGOs, who, when, where and how" should start any CBR activities in Vietnam